The Taylorist / Fordist plant and platform capitalism: the gears of labor exploitation - Chaves, Andréa Bittencourt Pires (Research, Society and Development, 2020)
This work analyzes the organizational changes implanted by capitalism to improve the forms of labor exploitation. The proposed objective was to discuss the successful changes in the organization / management of work from Taylorism / Fordism to Platform Capitalism. The methodological procedure was a qualitative approach with a review of the literature relevant to the study. It started from the explanatory readings of the capital / labor contradiction, through the production of new technologies, in the direction of the real subsumption of work to capital highlighted in Marxist theory. The theoretical proposal supports understanding the formation of work on demand in platform capitalism in place of the protected work of the Taylorist / Fordist Model. The result points to transformations in favor of capital having as a principle the dismantling of labor rights. It was possible to conclude that the work, already precarious, reaches even more perverse levels of precariousness in the farce of the self-employed worker of services by applications, developed by platform capitalism.